ANALISIS PERLINDUNGAN HUKUM TERHADAP NASABAH YANG TIDAK MAMPU MEMBAYAR ANGSURAN BANK DITINJAU DARI UNDANG-UNDANG NO 10 TAHUN 1998 TENTANG HUKUM PERBANKAN (CONTOH KASUS PUTUSAN NO 646K/PDT/2017) - Jennisyah Alya; Jeane Neltje (Fakultas Hukum Universitas Tarumanagara, 2021)
In other countries or in Indonesia, we have often heard the term borrowing or borrowing what we usually call credit. Credit is one of the facilities provided by banks for people who are less able to roll their money back. Based on the contents in this thesis, there are problems, namely how legal protection and good billing procedures are for customers who are unable to pay bank installments in the decision no. 646K/PDT/2017 in terms of Banking Law No. 10 of 1998, then the research objectives in this thesis theoretically, the author hopes that the results of this paper can provide benefits and contribute to knowledge in civil law, especially those related to banking. Practically, the author hopes that the results of this writing can be useful for information and consideration, input to the general public, and officials who apply in general. In addition, it is also hoped that after this research is made, parties who can carry out banking supervision are even better. Based on the research data as follows: That on November 14, 2011, Plaintiff II, namely Mr. Afiat Dwihana Fakhrudhi who resides in Glagaharum hamlet RT/RW 005/002, Dukuharum Village, Megaluh District, Jombang Regenc.